A European clustering study with Knowledge Transfer Office DNA. (9th November 2020) - Kreiling, Laura; Scanlan, John
This research presents a novel approach to cluster knowledge transfer organisations (KTOs) using reported metrics which capture their fundamental characteristics. Currently, organisational comparisons are conducted in some national contexts. However, European KTOs cannot easily find their international peers, due to the lack of suitable approaches. To address this, a conceptual framework - 'KTO DNA' - with 11 quantitative variables is developed and tested. It enables determining KTO similarity based on key drivers of KT activity: budget for KT, structural characteristics, internal KT culture and external KT ecosystem. This framework is used in a cluster study with datasets from a transnational European KTO database. Initial analysis resulted in five groups, a within-clustering of the largest group in seven international KTO peer groups. Variables related to the internal KT culture primarily drove cluster creation, followed by external KT ecosystem and KT budget. KT structural characteristics proved useful in some clusters for further analysis.